Effect of cefodizime, ofloxacin, ciprofloxacin and interferon alpha-2a, alone and in combination, on phagocytic and candidacidal functions of leucocytes from patients with chronic renal failure - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1999)
We have examined the effects of cefodizime, ofloxacin, ciprofloxacin and interferon alpha-2a (IFN alpha-2a), alone and in combination, on phagocytosis and killing of Candida albicans blastospores by polymorphonuclear leucocytes (PMNs) from patients with chronic renal failure. The effects of therapeutic concentration of each drug on the phagocytic and candidacidal capacity were studied in vitro. 20 chronic renal failure patients, average age 45, were included. Phagocytosis and candidacidal capacity were significantly enhanced (P < 0.001) after pre-treatment of PMNs with cefodizime at 10 mu g/ml, but ofloxacin (4 mu g/ml) and IFN alpha-2a (10 U/ml) had no effect compared to the control with no antibiotics. However, only candidacidal capacity increased significantly with ciprofloxacin at 2 mu g/ml (P < 0.001). In contrast, ciprofloxacin had no significant effect on phagocytosis (P > 0.05). Combinations of these three drugs with IFN alpha-2a produced the same effect as these two drugs alone. These results indicate that cefodizime, ofloxacin and ciprofloxacin alone and in combination with IFN alpha-2a at safely achievable concentrations generally do not suppress PMN function in vitro. Med Sci Res 27:315-318 (C) 1999 Lippincott Williams Wilkins.
Keywords: cefodizime; ofloxacin; ciprofloxacin; interferon alpha-2a; chronic renal failure; phagocytic and candidacidal function; HUMAN POLYMORPHONUCLEAR LEUKOCYTES; RESPIRATORY BURST; IN-VITRO; ANTIBIOTICS; INVITRO; AGENTS